Myocardial Bridging in Sports and Exercise Cardiology: Screening Challenges, Clinical Management, and Physical Activity Guidance - Jonathan C. Spaan; Sean P. Swearingen (Journal of Clinical Medicine, 2026)
Myocardial bridging (MB) is a congenital coronary anomaly in which a segment of an epicardial coronary artery courses intramurally beneath the myocardium for part of its length, resulting in dynamic compression during systole. Once considered a largely benign incidental finding, accumulating evidence has demonstrated MB to be a clinically significant substrate for myocardial ischemia, arrhythmia, and sudden cardiac death (SCD), particularly under conditions of elevated adrenergic drive such as vigorous physical exercise. The prevalence of MB is highly dependent on the diagnostic modality used, ranging from approximately 0.5–2.5% on coronary angiography to 15–85% on post-mortem and advanced intravascular imaging studies, reflecting a substantial detection gap- in particular on routine cardiac screening tests. This review critically examines the current evidence base regarding MB in the context of competitive and recreational sport. We address: (1) the pathophysiology of exercise-induced hemodynamic compromise in MB; (2) the limitations of existing screening modalities—including electrocardiography, echocardiography, exercise stress testing, and advanced coronary imaging in identifying athletes at risk; (3) the clinical management of symptomatic MB, encompassing pharmacological therapy, coronary revascularization strategies, and catheter-based interventions; and (4) physical activity guidance for athletes with known or suspected MB.